Compressibility and thermoelasticity of CrN. Issue 3 (2nd July 2020) - Yan, Mingqi; Zhou, Xuefeng; Cheng, Hu; Wang, Liping; Zhang, Jianzhong; Yu, Xiaohui; He, Duanwei; Mei, Jia-wei; Zhao, Yusheng; Wang, Shanmin
ABSTRACT: We report experimental determination of compressibility and thermoelasticity for CrN based on in situ high pressure/high temperature synchrotron x-ray diffraction measurements. The pressure-induced cubic-to-orthorhombic phase transition is observed at ∼ 5 GPa in high-quality CrN samples synthesized using a high pressure reaction route. Equation of state, bulk modulus and axial compressibility of this material are obtained by analysis of high pressure x-ray diffraction data collected at room temperature. Both cubic and orthorhombic phases have a similar bulk modulus value of 257 (5) and 262 (6) GPa, respectively. For orthorhombic CrN, the b -axis has the most axial incompressibility, which should be associated with magnetic properties. In addition, the isothermal equation of states is also determined at different temperatures of 300, 400, 600, 800, 1000, and 1200 K, respectively. Some of the important thermoelastic properties of cubic CrN are thus derived, including temperature derivative of bulk modulus ∂ K T / ∂ T = − 2.95 ( 5 ) × 10 − 2 G P a ⋅ K − 1 and volumetric thermal expansivity a T ≈ a 0 + a 1 ⋅ T where a 0 = 1.95 (16) × 10 −5 K −1 and a 1 = 4.39 (3) × 10 −9 K −1 .